Encyclopedia of GIS - Shekhar, Shashi 1963-; Xiong, Hui (Springer, 2008)
Entries explain the key software, data sets, and processes used by geographers and computational scientists. Includes major overviews on topics, such as geoinformatics, spatial cognition, and location-based services. Shorter entries define specific terms and concepts, such as the global positioning system, digital elevation/terrain model, and remote sensing.